Sensor eletroquímico baseado em eletrodo nanoporoso para detecção e quantificação de trans-resveratrol - Klein, Rosecler Scacchetti (2020)
The study on antioxidants has gained prominence due to the beneficial effects on human health. Thus, their quantification in their natural or artificial sources is of great importance. Among the main antioxidants, trans-resveratrol (T-RESV) has been highlighted. It is a natural polyphenolic antioxidant generally found in grapes and also in its derivatives such as red wine and grape juices. This bioactive is responsible of in very important activities in the human body such as antiinflammatory, antiplatelet, estrogenic properties, and acts by strengthening muscle fibers. Conventionally, antioxidants are determined by chromatographic techniques or capillary electrophoresis. However, these techniques are complex, require large amounts of reagents, and require a lot of analysis time. Recently, studies show that electrochemical sensors have gained prominence because they overcome the drawbacks of traditional techniques, standing out in the speed of analysis, relatively low cost, potential for miniaturization and high sensitivity. In addition, these devices can be conditioned for the detection of specifc antioxidants to avoid false responses. It has also been shown that the presence of conducting nanomaterials, particularly gold nanoparticles (AuNPs) and graphen,. optimize the device analytical response. In this sense, it was proposed here to build an electrochemical sensor that was applied for detection of T-RESV. This sensor operated with a glass-ITO electrode covered with nanoporous gold films. The electrodes were modified with a composite of gold nanoparticles, nafion, and -cyclodextrin (-CD). Analysis by SEM/EDS and FTIR showed that a homogeneous film of the composite was obtained on the electrode from the dripping of an aqueous mixture of chemical species. In addition, it was possible to verify that nafion effectively acts as a support for AuNPs and -CD, so that they were not leached from the electrode surface. Electrochemical impedance spectroscopy (EIS) tests have shown that AuNPs play an important role in improving electrode conductivity, since the charge transfer resistance decreases with their presence. Detection tests by cyclic voltammetry (CV) showed that the presence of -CD (recognition agent) in the composite is essential because, in its absence, it was not possible to detect T-RESV. Thus, -CD had an important effect of recognition and adsorption of the target analyte for its detection on the electrode. The sensor presented excellent analytical parameters, when compared with other sensors of the same nature reported in the literature. The sensitivity value was 1,69 µA/nmol.L-1 ,and the LD was 0,785 nmol /L. Thus, we show here the production of a sensor with excellent analytical performance that can open new perspectives for selective detection of T-RESV.